Toxicity and symptomatic identification of species involved in snakebites in the Indian subcontinent - Kumar,V. (2006)
Snakebites, being the major occupational hazard for farm workers, claim a large number of lives in the Indian subcontinent. During the course of medical management, identification of the biting species is given a low priority, resorting to prescription of polyvalent anti-snake venom. Whereas the World Health Organization (WHO) recommends monospecific anti-snake venom instead of polyvalent anti-snake venom. Thus, it is essential to identify the aggressor species either by a visual inspection or by the symptoms of the victim. Along with the four deadly venomous species (cobra, krait, Russell's viper, and saw-scaled viper), there are a number of other species of medical importance, whose venoms and bites have not been paid much attention. Thus, a misclassification resulting into erroneous treatment cannot be ruled out. This paper discusses the nature, constitution, and toxicity of venoms and their possible toxic effects on victims of snakebites. An attempt has also been made to categorize the distinctive symptoms due to the bites of the four major venomous species and their severity grading.